Peran Guru PAI dalam Menanamkan Nilai-Nilai Multikultural dan Moderasi Beragama di SMK Bengkulu Utara - Ajamalus, Ajamalus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This article explores the strategic role of Islamic Religious Education (PAI) teachers in instilling multicultural values and religious moderation in schools, particularly at SMK Negeri 1 Argamakmur Bengkulu Utara. The study is based on the reality of Indonesia’s cultural and religious diversity, which, if unmanaged, may lead to social conflict. Using a qualitative descriptive method and a case study approach, the findings reveal that PAI teachers carry out three primary roles: as motivators, administrators, and evaluators. Teachers not only impart peaceful and tolerant religious understanding but also shape students’ character to live harmoniously in a pluralistic society. The research also identifies several influencing factors, such as parenting styles, globalization, and the limited depth of Islamic scholarship, which affect the success of cultivating religious moderation. Therefore, a synergy among educational institutions, families, and communities is essential to foster a generation that is tolerant and morally upright.